Acceptance of an innovation toward performance within construction industry - Ainaa Farhana, Rosli (2015)
This study is to determine acceptance an innovation towards performance in Construction Company and identify an obstacle on acceptance an innovation towards Construction Company. Both of the objectives have huge influence to construction industry. Therefore, acceptance innovation give an impacts towards the construction industry/company. The obstacles can affected the construction industry difficult to accept new technology. The population of this study is 75 of selected contractor under Grade 7 registered with Construction Industry Development Board of Malaysia (CIDB) at Kuantan, Pahang Darul Makmur. The sample size is use as the units of analysis, 63 selected contractors which were from executive position was selected. In conducting this study, random sampling survey method was being used and this questionnaires survey was distributed to respondent by email and face to face. For the data analysing, this data was carried out by using Descriptive statistic is drawn from Statistical Package Social Science (SPSS) outputs. The finding from this study shows that an obstacles cause the construction industry/company towards acceptance an innovation itself.